UKRAINIAN PUBLIC PHILOSOPHY IN SEARCHING FOR A PUBLIC - Ovcharenko, Svitlana (International Journal of Innovative Technologies in Social Science, 2022)
Purpose. The aim of the article is to analyze the state and development of public philosophizing practices in Ukraine in modern technological and socio-cultural conditions. Theoretical basis. The author proposes to proceed from the fact that the removal of philosophical thought is an act of social communication, which becomes a cultural event and has signs of performativity with its aesthetic characteristics. Based on this, the process of social functioning of philosophy can be considered not only as a set of ideas and concepts but also as a set of performative practices in public spaces that correlate with the relevant historical and cultural contexts. The concept of "public philosophy" is difficult to unambiguously define, especially in the formation of a new paradigmatic field for social communication in substantive and formal aspects. Originality. The article analyzes the process of self-awareness of tasks, content, and formats of public philosophy in the professional philosophical environment of Ukraine in the period 2014-2021 and formed a methodological position, which suggests outlining the phenomena and meanings of public philosophy to take into account both substantive and performative features. Conclusions. Analysis of the "public turn" in Ukrainian philosophy forms a new topic for research that should find meaning based on both the modern sociocultural reality of Ukraine and the prospects of general technological renewal of communication: 1) philosophy as a fundamental basis for forming a postdisciplinary paradigm of interaction areas of knowledge; 2) performative aspect of philosophical public communication; 3) the relationship between public and practical philosophy in the context of the analysis of cultural practices.